Uji Aktivitas Berbagai Tumbuhan Terhadap Escherichia coli: Systematic Review: Uji Aktivitas Berbagai Tumbuhan Terhadap Escherichia coli: Systematic Review - Haifa Nabila; Devina Asbiya Pratama; Habil Firmansyah; Rahma Siti Aliya; Weni Febi Maharani; Firman Muharam; Yogi Rahman Nugraha; Mamay (Jurnal Medika Farmaka, 2026)
Introduction: Escherichia coli (E. coli) is a major pathogen causing diarrhea and urinary tract infections in Indonesia, and increasing antibiotic resistance necessitates the exploration of natural alternatives from local biodiversity. Methods: This systematic review analyzes ten in vitro experimental research articles (2020–2024) that tested the antibacterial activity of various Indonesian plant extracts against E. coli. The methods used were disc diffusion (Kirby–Bauer) and well diffusion. Results: Lemon peel (Citrus limon L.) extract exhibited the highest inhibitory activity against E. coli, followed by guava leaf (Psidium guajava L.) and Meistera chinensis stem extracts, which also demonstrated strong antibacterial effects. A consistent dose-response relationship was identified, with larger inhibition zones at higher extract concentrations. Key secondary metabolites identified include flavonoids and tannins. Other plant extracts, such as noni leaf (Morinda citrifolia L.), breadfruit leaf (Artocarpus altilis), turmeric (Curcuma domestica), cinnamon (Cinnamomum burmannii), and sungkai leaf (Peronema canescens), also contributed to antibacterial activity, although to varying degrees. Conclusion: Various Indonesian plant extracts, particularly lemon peel, guava leaf, and M. chinensis stem, show promise as natural antibacterial agents against E. coli. These findings warrant further research on active compound isolation, toxicity testing, and formulation development to complement conventional therapies. Keywords: Escherichia coli, plant extracts, antibacterial, disc diffusion, well diffusion.